DESIGN AND BUILD AN AQUARIUM PROTOTYPE BASED ON (IOT) INTERNET OF THINGS - Wan Pujitami Permata; Muhammad Nasir; Aswandi; Malvina Marchese (PT. Radja Intercontinental Publishing, 2023)
The problem and obstacle currently experienced by aquarium users is that users have to check the condition of the food and water conditions by coming directly to the aquarium. This method can be annoying and waste a lot of the user's time working and it is certainly not easy if every time the user has to directly check the condition of the feed and water in the aquarium. So from this problem I designed a system, namely designing an aquarium prototype based on IoT (internet of things) which can help with the problems being faced by aquarium users. This system is a sophisticated manual system using Arduino Wemos D1, Turbidity sensors and Proximity sensors to determine the condition of fish food and water conditions in the aquarium. With this system, it can make it easier for users to know the condition of the feed and water conditions in the aquarium, so that the user's time is not wasted and the user does not need to bother taking care of the condition of the aquarium. From the results of water testing using the Turbidity sensor, the values ​​for very turbid water conditions were 266, 272, 281, 283, turbid water 518, 526, 536, 544 and clear water 589, 590, 594, 595. In the Proximity sensor test, the has a value of 1 when the sensor detects the presence of food and the sensor has a value of 0 when it does not detect the presence of food.